2018
DOI: 10.3390/su10020522
|View full text |Cite
|
Sign up to set email alerts
|

CSR Performance, Financial Reporting, and Investors’ Perception on Financial Reporting

Abstract: This study examines whether socially responsible firms behave differently from other firms in their financial reporting. Specifically, we question whether firms that are better in their corporate social responsibility (CSR) performance also behave in a responsible manner to maintain their financial reporting quality and whether the market rewards such responsible behaviors. Using data from S&P 500 US companies, we find that socially responsible firms are less likely to manage their earnings. However, we fail t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 45 publications
1
45
1
Order By: Relevance
“…They used institutional ownership, analyst following, board independence, and audit committee independence and found that the coefficients of the intersection variables between the first few years dummy and the governance variables were negative and statistically significant. As more earnings manipulation means less CSR investments [32][33][34], we expected a similar moderating effect of governance on the relationship between tenure and CSR. Unlike Ali and Zhang [8], who did not test the governance effect for the last year, we predicted the moderating effect of governance also on the horizon problem.…”
Section: Hypothesismentioning
confidence: 77%
See 2 more Smart Citations
“…They used institutional ownership, analyst following, board independence, and audit committee independence and found that the coefficients of the intersection variables between the first few years dummy and the governance variables were negative and statistically significant. As more earnings manipulation means less CSR investments [32][33][34], we expected a similar moderating effect of governance on the relationship between tenure and CSR. Unlike Ali and Zhang [8], who did not test the governance effect for the last year, we predicted the moderating effect of governance also on the horizon problem.…”
Section: Hypothesismentioning
confidence: 77%
“…Ali and Zhang [8] tested the two periods and discovered that in both periods CEOs increase discretionary accruals and reduce discretionary expenses. As an increase in earnings management decreases CSR [32][33][34], and CSR investment can be one type of discretionary expenditure CEOs want to minimize at the time of short-termism, we expected that the effect of these periods on CSR would be similar to that of Ali and Zhang [8]. Because a manager who wants to maximize his/her short-term profit may not have room for allowing expenditures in a long-term project such as CSR, CSR investment will be decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the AMCs' performance we used several indicators already adopted in the literature: (a) two accounting‐based measurement return on asset (ROA) ratio and return on equity (ROE) ratio as a profitability proxy of an AMC (Tsoutsoura, ) and (b) a financial‐based measurement using asset turnover ratio (Timbate & Kyu Park, ).…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have used two accrual models to measure earnings quality, including discretionary accruals model [107] and non-discretionary accruals [108]. Additionally, a significant number of studies [34,50,[109][110][111] have found a negative relationship between various BOD characteristics and abnormal accruals. Similarly, by using the absolute value of discretionary accruals, [112] examined the relationship between IC and EM in Australian firms; their results suggested that a low level of EM is associated with the presence of non-executive directors on the BOD.…”
Section: Dependent Variablesmentioning
confidence: 99%